Optimal approximation of linear systems using a Teaching-Learning-Based Optimization algorithm - Yu, Guolin; Zhang, Qingyang; Song, Hui (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In simulation of complex dynamic system or controller design, approximation of linear system models is one important task. In this paper, an optimization algorithm named Teaching-Learning-Based Optimization (TLBO) is presented for optimal approximating linear systems. The novel algorithm performance was tested on two linear systems, a stable linear system and an unstable one. Experimental results show that the proposed TLBO can effectively approximate stable and unstable linear systems.